JUSTIFIKASI KEBIJAKAN PEMERINTAH KOTA PONTIANAK DALAM MEMBERIKAN PELUANG PEKERJAAN BAGI PENYANDANG DISABILITAS - Martoyo, Martoyo; Herlan, Herlan; Sukamto, Sukamto; Sikwan, Agus; Elyta, Elyta; Vayed, Dodi Al (Jurnal Ilmu Sosial dan Ilmu Politik (JISIP), 2023)
This study intends to offer recommendations to the Pontianak City regional administration for improving employment regulations for people with disabilities in Pontianak City. The opportunities for people with impairments are the same as those for everyone else. The Pontianak City Government has created policies for people with disabilities to meet their requirements. The local laws outline the rights of people with disabilities, including the right to employment. These regional regulations have been put into effect by the Pontianak City Government through the Pontianak City Manpower, Cooperative, and UKM Office, starting with the management of information on the world of work for people with disabilities, work facilities, skill training, and awareness of the rights of workers with disabilities. Defects continue to be found in its application, making executing these policies less than ideal. Based on the study's findings, the Regional Government of Pontianak City adopted the Regional Regulation of the City of Pontianak Number 13 of 2013 concerning the Protection and Empowerment of Persons with Disabilities in Pontianak City, which established an employment policy for people with disabilities. The Regional Government of Pontianak City has made several efforts to put the law into practice, starting with information management, work facilities, skill training, outreach, awareness programs for the law's rights, and information about the employment of people with disabilities in Pontianak City.Penelitian ini bertujuan menawarkan rekomendasi kepada pemerintah daerah Kota Pontianak untuk penyempurnaan peraturan ketenagakerjaan bagi penyandang disabilitas di Kota Pontianak. Kesempatan bagi orang-orang dengan gangguan sama dengan kesempatan untuk orang lain. Pemerintah Kota Pontianak telah membuat kebijakan bagi penyandang disabilitas untuk memenuhi kebutuhan mereka.. Undang-undang setempat menguraikan hak-hak penyandang disabilitas, termasuk hak atas pekerjaan. Peraturan daerah ini telah diberlakukan oleh Pemerintah Kota Pontianak melalui Dinas Tenaga Kerja, Koperasi, dan UKM Kota Pontianak, dimulai dengan pengelolaan informasi dunia kerja bagi penyandang disabilitas, fasilitas kerja, pelatihan keterampilan, dan kesadaran akan hak-hak pekerja penyandang disabilitas. Cacat terus ditemukan dalam penerapannya, membuat pelaksanaan kebijakan ini kurang ideal. Berdasarkan temuan penelitian, Pemerintah Daerah Kota Pontianak mengadopsi Peraturan Daerah Kota Pontianak Nomor 13 Tahun 2013 tentang Perlindungan dan Pemberdayaan Penyandang Disabilitas di Kota Pontianak, yang menetapkan kebijakan ketenagakerjaan bagi penyandang disabilitas. Pemerintah Daerah Kota Pontianak telah melakukan beberapa upaya untuk menerapkan undang-undang tersebut, mulai dari pengelolaan informasi, fasilitas kerja, pelatihan keterampilan, penjangkauan, dan program kesadaran akan hak-hak hukum, serta informasi tentang ketenagakerjaan penyandang disabilitas di Kota Pontianak